Vascular Surgery Cases, Questions and Commentaries - Geroulakos, George; Sumpio, Bauer; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
This updated and revised third edition of Vascular Surgery: Cases, Questions and Commentaries provides a unique collection of real-life case histories, written by experts, that highlights the diversity of problems encountered in vascular surgery. With an international panel of contributors, many of whom are also examiners on the UK, European or American Boards in Vascular Surgery, this book familiarizes the reader quickly with day-to-day clinical practice. Case studies are presented in question-and-answer format and have been widely referenced to reassure the reader that their contents are established best practice. Most cases are accompanied by multiple x-rays or color illustrations for visual clarity. This book serves as a teaching resource for vascular trainees or practitioners who are reviewing for the oral board exam or practitioners who wish to refresh their expertise with an interactive source of information. It also provides established practitioners the wherewithal to review the current standards of practice in vascular surgery.
Section I:Arterial Aneurysms -- Preoperative Cardiac Risk Assessment and Management of Elderly Men with an Abdominal Aortic Aneurysm -- Abdominal Aortic Aneurysm -- Endoluminal Treatment of Infra-renal Abdominal Aortic Aneurysm -- Ruptured Abdominal Aortic Aneurysms -- Thoracoabdominal Aortic Aneurysm -- Endovascular Management of Thoracic Aneurysm -- Aortic Dissection -- Popliteal Artery Aneurysms -- Renal Artery Aneurysm -- Anastomotic aneurysms -- False Aneurysm in the Groin Following Coronary Angiography -- Acute Thrombosis -- Section II: Acute Ishaemia -- Arterial Embolism -- Blast Injury to the Lower Limb -- Endovascular Management of Aortic Transection in a Multiinjured Patient -- Section III: Management Of Chronic Ischaemia of the Lower Extremities -- Cardiovascular Risk Factors and Peripheral Arterial Disease -- Endovascular Management of Lower Limb Claudication due to Iliac Artery Occlusive Disease -- Lower Limb Claudication due to Bilateral Iliac Artery Occlusive Disease: The Case for Iliac Stenting and Femorofemoral Crossover Bypass -- Endovascular Management of Lower Limb Claudication due to Infra- Inguinal Disease -- Endovascular Management of Non-Healing Leg Ulceration -- Bypass to the Popliteal Artery -- Bypass to the Infrapopliteal Arteries for Chronic Critical Limb Ischaemia -- Popliteal artery entrapment -- Adventitial Cystic Disease of the Popliteal Artery -- The Oburator Foramen Bypass -- Diabetic Foot -- Section IV: Surgery of the Major Branches of the Infradiaphragmatic Aorta -- Chronic Visceral Ischaemia -- Acute Messenteric Ischaemia -- Renovascular Hypertension -- Midaortic Syndrome -- Section V: Management of Popliteal Hypertension -- Management of Portal Hypertension -- Section VI: Management of Extracranial Cerebrovascular Disease -- Management of Carotid Bifurication Disease -- The Carotid Body Tumor -- Takayasu Arteritis Associated with Cerebrovascular Ischemia -- Takayasu Arteritis Associated with Cerebrovascular Ischemia -- Section VII: Neurovascular Conditions of the Upper Extremity.-Neurogenic Thoracic Outlet Syndrome and Pectoralis Minor Syndrome -- Acute Axilliary/Subclavian Vein Thrombosis -- Raynaud's Phenomenon -- Section VIII: Prevention and Management of Complications of Arterial Surgery -- Aortofemoral Graft Infection -- Aortoenteric Fistulas -- Section IX: Vascular Access -- The Optimal Conduit for Hemodialysis Access -- Acute Ischaemia of the Upper Extremity Following Graft Aortovenous Fistula -- Section X: Amputations -- Amputations in an Ischemic Limb -- Section XI: Vascular Malformations -- Congenital Vascular Malformation -- Klippel-Trenaunay Syndrome -- Section XII: Management of Venous Disorders -- Deep Venous Thrombosis -- Endoluminal Ablation of Varicose Veins -- Ultrasound Guided Foam Sclerotherapy for the Management of Recurrent Varicose Veins -- Venous Ulcers Associated with Deep Venous Insufficiency -- Venous Ulcers Associated with Superficial Venous Insufficiency -- Iliofemoral Venous Thrombosis -- Ileofemoral Venous Thrombosis During Pregnancy -- Section XIII: Lymphodema -- Management of Chronic Lyphedema of the Lower Extremity -- Management of Upper Extremity Lymphedema with Microsurgical Lympho-venous Anastomosis (LVA).
Keywords: Medicine; Angiography; Surgery; Vascular Surgery; Medicine & Public Health; Vascular Surgery; Surgery; Angiology